Реализация когнитивных мотивов в русских и польских названиях банковских вкладов - Jóźwiak, Jolanta (Acta Polono-Ruthenica, 2018)
The paper attempts to identify the most frequent cognitive motives used in nomination of Russian and Polish deposit accounts. The aim is also to state differences between Russian and Polish such kind of business communication. Many groups of lexems were analised and it shows which motives were prefered by the specialists of naming. Author also presents which motives are reccurent in Russian and Polish, which related to the process of globalization in advertising and the motives of which reveal cultural specificity.